Pola Distribusi Zakat Produktif: Pendekatan Maqasid Syari'ah dan Konsep CSR - Muhammad Yasir Yusuf (Media Syari'ah, 2017)
This paper aims to discuss the pattern of the distribution of the zakat funds productively to provide better impact for recipients. The problem of this study is how the concept of distribution of Zakat funds were duly carried out by the charity institution that is able to empower the poor. The study used two approaches. First: observations on the pattern of distribution of zakat is done by Baitul Mal Aceh. Second: literature approaches to see which Zakah bentukpendistribusian memberikandampak better approach maqasid Shari’ah and the concept of CSR. The study concluded, first; micro financing through productive charity run by the Baitul Mal Aceh became one of the effective model and alternative bagimemberdayakan poor. second; Shari’ah maqasid approach and the concept of CSR can be used as a concept for zakat (alms collectors) in zakat mendistribusikandana productive. The approach also provides a way out for charity managers to choose mustahik are a top priority in order to obtain the allocation of zakat funds for charity mustahik freed from poverty